Not in our school creating a non-bullying culture - Sleeth, Shannon; Collins, Cath; Garner, Simon; Leigh, Richard; Video Education Australasia (Australia : Video Education Australasia, 2005)
This program looks at the whole school approach to bullying. This approach focuses on a school's formal curriculum and classroom practices and involves all members of the school community. Also highlights the steps to building a safe school, skills-building for students, peer support systems and student-directed campaigns
Title from title screen
Executive producer, Mark McAuliffe
Voice over: Chris Adamidis
DVD Format
Keywords: Bullying in schools; Bullying